2007
DOI: 10.1371/journal.pone.0001071
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of a Poly(ADP-Ribose) Polymerase-1 Inhibitor on Experimental Arthritis by Downregulating Inflammation and Th1 Response

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) synthesizes and transfers ADP ribose polymers to target proteins, and regulates DNA repair and genomic integrity maintenance. PARP-1 also plays a crucial role in the progression of the inflammatory response, and its inhibition confers protection in several models of inflammatory disorders. Here, we investigate the impact of a selective PARP-1 inhibitor in experimental arthritis. PARP-1 inhibition with 5-aminoisoquinolinone (AIQ) significantly reduces incidence and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 29 publications
3
35
0
9
Order By: Relevance
“…Recently, it was discovered that Th17, rather than Th1, cells are involved in the pathogenesis of inflammatory diseases, including experimental autoimmune encephalomyelitis (EAE) (28). PARP-1 plays a crucial role in the progression of inflammatory responses (24,25), and its inhibition confers protection in EAE (3). We found that purified PARP-1 KO naive CD4 cells differentiated into Th17 cells, produced IL-17, and expressed RORgt mRNA as well as WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was discovered that Th17, rather than Th1, cells are involved in the pathogenesis of inflammatory diseases, including experimental autoimmune encephalomyelitis (EAE) (28). PARP-1 plays a crucial role in the progression of inflammatory responses (24,25), and its inhibition confers protection in EAE (3). We found that purified PARP-1 KO naive CD4 cells differentiated into Th17 cells, produced IL-17, and expressed RORgt mRNA as well as WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Інгібування ПАРП запо-бігало та послаблювало запальний процес в експериментальних моделях аутоімунних і запальних захворювань (при хворобі Пар-кінсона, аутоімунному нефриті, хронічному запаленні кишечника, експериментальному алергічному енцефаломієліті, аутоімунному гепатиті, експериментальному ураженні ле-гень, за умов контактної гіперчутливості, на моделях септичного і геморагічного шоку та ін. [5][6][7][8][9][10]. Хоча розвиток різних імунопато-логічних процесів супроводжується й опо-середковується формуванням і відкладанням імунних комплексів (IК) у тканинах, однак роль ПАРП у патогенезі імунокомплексних хвороб вивчено недостатньо.…”
Section: вступunclassified
“…Ви-хід клітинного вмісту назовні, в свою чергу, сильно активує клітини-ефектори запалення зі збільшенням синтезу прозапальних цито-кінів, реактивних форм кисню та азоту, що посилює генотоксичний стрес та активацію ПАРП. Відповідно, інгібування ПАРП пере-риває цей патологічний процес посилення запалення й виявляє протективну дію, в тому числі й при деяеих імуноопосередкованих хворобах [5][6][7][8][9][10]. Блокатор ПАРП 4-ГК мав виражений цитопротективний ефект за умов імунокомплексної патології: покращувався морфофункціональний стан ІКК, збільшува-лась їх життєздатність внаслідок послаблення некрозу, суттєво зменшувалось ушкодження ДНК.…”
Section: влияние ингибитора поли (адф-рибоза) полимеразы 4-гидроксик-unclassified
“…It has reported that PARP-1 mostly plays a key role in cell death following numerous inflammation situations such as ischemia reperfusion damage [61], haemorrhagic shock, septic shock [62], lung inflammation [63], diabetes mellitus [64], autoimmune nephritis [65], chronic inflammatory disorders such as arthritis and IBD [66], and diseases of the central nervous system [67]. PARP-1-deficient mice showed decreased PARP-1 expression, a significant parameter in the endothelial dysfunction pathogenesis of diabetes [64], regulates the progression of autoimmune nephritis [65].…”
Section: The Role Of Nfkb1 and Parp-1 Inflammatory Diseasementioning
confidence: 99%